1998
DOI: 10.1046/j.1365-2362.1998.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of growth hormone (GH) and insulin‐like growth factor I and II (IGF‐I and ‐II) on chromosome fragility and p53 protein expression in human lymphocytes

Abstract: These results indicate that the DNA-damaging effect of BLM is amplified by GH and, more markedly, IGF-I and -II. IGF-I and -II also stimulate p53 protein expression that, taking part in DNA repair, may counteract the IGF action on genome stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 37 publications
(47 reference statements)
2
18
0
Order By: Relevance
“…Although there is some in vitro experimental evidence of a possible association between GH1 and breast carcinoma, [7][8][9][10] no positive epidemiologic findings have been reported since 1985, when a small casecontrol study reported an elevated concentration of GH1 in sera obtained from patients with breast carcinoma. 11 Although two recent prospective epidemiologic studies demonstrated that high circulating GH1 concentrations and GH1 treatment are significantly associated with an increased risk of malignancy, 21,22 no association with breast carcinoma risk was found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is some in vitro experimental evidence of a possible association between GH1 and breast carcinoma, [7][8][9][10] no positive epidemiologic findings have been reported since 1985, when a small casecontrol study reported an elevated concentration of GH1 in sera obtained from patients with breast carcinoma. 11 Although two recent prospective epidemiologic studies demonstrated that high circulating GH1 concentrations and GH1 treatment are significantly associated with an increased risk of malignancy, 21,22 no association with breast carcinoma risk was found.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that GH1 increases expression of insulinlike growth factor I (IGF-I) and IGF-I binding protein 3 (IGFBP-3), 2,4 both of which may be related to breast carcinoma risk. 2 It also has been reported that GH1 may increase chromosome fragility both in vitro and in vivo 7 and may increase the expression and transcriptional activity of the oncogene HOXA1. 8 It was found that GH1 gene expression and GH1 protein concentrations were much higher in progressive proliferative disorder tissue samples compared with normal mammary gland tissue samples.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Suggested hypotheses include genetic factors, energy intake in early life, and exposure to sex and growth hormones. For instance, insulin-like growth factor-I is associated with height and also inhibits apoptosis of damaged cells and stimulates cell turnover and cell proliferation (8,72,73). Insulin-like growth factor-I was associated with an increased risk of ovarian cancer before age 55 in one study (74).…”
Section: Anthropometry and Ovarian Cancer Cancer Epidemiol Biomarkersmentioning
confidence: 97%
“…However, it is plausible that mammotrophic factors such as hGH in executing their physiological roles may simply utilize CHOP to mediate cell survival and that the subsequent failure to undergo programmed cell death, in situations of cellular injury associated with DNA damage, would result in carcinoma (72). It is therefore interesting that the DNA-damaging effect of bleomycin in human lymphocytes is enhanced by hGH (73); and hGH and the related hormone prolactin have both been implicated in the development of mammary carcinoma (74). It is also interesting that GH itself has also been reported to be both mitogenic and growth inhibitory depending on the cellular context (75).…”
Section: Effect Of Chop Overexpression In Mammary Carcinoma Cells On mentioning
confidence: 99%